PERSEPSI KETERTARIKAN INTERPERSONAL PADA GAYA BERPAKAIAN GURU DI JAKARTA TIMUR - Gumelar, Gumgum; Haris, Abdul (Universitas Persada Indonesia YAI, 2018)
The purpose of this research is to determine whether there are differences in studentâsattractiveness perception in elementary schoolâs teacher based on the teacherâs clothing style in the villageof Pondok Kelapa, East Jakarta. This research uses pre-experimental research method with sample quotatechnique and questionnaire as a data collecting technique. This experiment was designed by manipulatingthe style of clothing of male and female teachers as a stimulus, which then sorted by the level of attractiveness on the likert scale. Subjects in this research were 100 people with an age range from 10 to 12 years old. The result of the analysis data of this research obtained F=29,270; p=0,000 < 0,05 (significant).So it can be concluded that the results of this research is there is a significant difference in studentâsattractiveness perception in elementary schoolâs teacher based on the teacherâs clothing style.